Analisis Faktor–Faktor yang Mempengaruhi Pemilihan Karir Mahasiswa Akuntansi Sebagai Akuntan Publik (Studi Empiris pada Mahasiswa S1 Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Pancasila) - Yetty Murni; Hotman Fredy; Mimi (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
The purpose of this study is to determine whether the factors of financial reward, work environment, social values and academic achievement affect the career choice of student majoring in accounting as public accountant. This research was conducted based on the inconsistent result of the previous research. The sample used in this study were students majoring in business accounting at the faculty economic and business of pancasila university. The the object of the study was 57 respondents.The analytical method used in this study is a multiple linear regression statistical analysis using SPSS version 25. The conclusion that can be obtained from this study is that social values and academic achievement have a significant effect on career choice as a public accountant while Financial awards and work environment do not affect the choice of career as a public accountant.